Outcome of Primary Pterygium Surgery Using the Inferior Conjunctival Autograft - Patel, Sushila; Godar, Manita Sunam; Pokharel, Binita Bhattarai (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION Pterygium is a common ocular condition with prevalence varying from 0.7-39% in different population and particularly high in the tropics. Various surgical techniques including inferior conjunctival autograft are available for the treatment of pterygium. This study was done to determine the clinical profile and outcome of primary pterygium surgery using inferior conjunctival autograft. MATERIAL AND METHODS This was a prospective, non-comparative interventional study conducted over a period of one year from January to December 2019 in patients with primary pterygium who presented at cornea department of Lumbini Eye Institute and Research Center, Bhairahawa, Nepal. All the patients with primary pterygium, a detail clinical history and examination were done. Pterygium was excised using inferior conjunctival autografting and followed regularly over a period of 3 months. RESULTS We analysed 626 eyes in 619 patients with primary pterygium in which mean age was 44.63 ± 13.84 years. There were 363 (58.64%) females. Majority of our patients were housewife 350 (56.54%) and farmer 170 (27.46%). Mean duration of presentation was 3.59 ± 2.87 year. Pterygium was found mostly on nasal side 614 (98.08%). Depending on the size, maximum patients had type 2 pterygium (73.80%) followed by type 3 pterygium (18.69%). The commonest post operative complication was raised intraocular pressure which was seen in 43 (6.87%) eyes and recurrence rate was 0.64%. CONCLUSION Primary pterygium was seen more commonly in adults in their 4th -5th decade of life with female predominance. Primary pterygium surgery using inferior conjunctival autograft is a safe and effective with very few complication and recurrence.